Impact of the use of three dimensions of a walker in the functional performance profile in institutionalized elderly - Parreira, Pedro; Lopes, Manuel; Fonseca, César (My University, 2019)
CISBETI 2019-International Congress of Health, Well-Being, Technology and Innovation. Foz de Iguaçu, Brazil. 4-6 April 2019. Foz de Iguaçu, Brazil. 4-6 April 2019.